Niveles de humus y su efecto en la captura de carbono en Vigna sesquipedalis (L) Fruwith (chiclayo verdura) en Zungarococha Iquitos-2023 - Villa Ramirez, Nicol Cristina (2024)
The experimental rehearsal settled in Zungarococha with the purpose of evaluating dose of worm humus and its repercussion in the agronomic characteristics and carbon of the Chiclayo greenness, the DBCA, the work was used it was experimental, they settled 20 beds of 2 x 5 m2 c/u, each one with 40 plants of the species in study, making a total of 800 plants, of each treatment took 4 plants like sample, tabulated the data and processed using the Software Infostad statistically, you reached the conclusion: that significant statistical significance exists in the studied variables of green matter, dry matter and accumulated carbon of the studied species, evaluated to the 60 days; the opposing values are: green matter T4 (5 kg/m2 of humus) it reports an average of (7.40 kg/m2), the T3 (4 kg/m2) I report (6.80 kg/m2), the T2 (3 kg/m2 =5 kg/m2 of biomass), the T1 (2 kg/m2 = 4.10 kg/m2) and the T0 (0 kg/m2 = 2.90 kg/m2). with regard to the dry matter: T4 (1.54 kg/m2), T3 (1.41 kg/m2), T2 (1.04 kg/m2), T1 (0.85 kg/m2) and T0 (0.60 kg/m2), with respect to the accumulated carbon T4 (0.59 kg/m2) for the T3 (0.54 kg/m2), for the T2 (0.40 kg/m2) for the T1 and (0.33 kg/m2) and for the T0 (0.23 kg/m2). For what the main hypothesis of work is accepted.